Mouhammad in the mirror of Islam, doctrines of Islam, G.B show on Islam, Glimpses of the prophet's life - Muhammad Husayn Tabataba'i (The World Forum for proximity of Islamic Schools of thought, 2007)
tr,1/ws.c.1